2018
DOI: 10.1111/jfbc.12589
|View full text |Cite
|
Sign up to set email alerts
|

Induction of gut Lactobacillus reuteri in normal ICR mice by oral administration of L. plantarum AN1

Abstract: To clarify the existence of indigenous intestinal gut bacteria sensitive to orally administered probiotic strains of lactic acid bacteria, the effects of live and heat‐killed Lactobacillus plantarum AN1 cells, administered to normal ICR mice via drinking water were observed. Amplicon sequencing of the 16S rDNA (V4) of caecal contents revealed that the live AN1 cells increased the abundance of an indigenous sensitive gut bacterium (SGB) Lactobacillus reuteri. From faecal samples, five typical dominant colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Bifdobacterium has a variety of probiotic functions, which can improve intestinal diseases caused by immune system disorders, secret antimicrobial peptides to enhance the intestinal barrier, and improve the activity of host antioxidant enzymes to alleviate oxidative stress damage [55]. While Lactobacillus can maintain microecological balance, inhibit the growth of conditioned bacteria in the intestinal tract, and improve body immunity [56]. Tese two probiotics can be rapidly grown using fructans like INU [57].…”
Section: Regulatory Efect Of Pcps On Intestinal Microbiotamentioning
confidence: 99%
“…Bifdobacterium has a variety of probiotic functions, which can improve intestinal diseases caused by immune system disorders, secret antimicrobial peptides to enhance the intestinal barrier, and improve the activity of host antioxidant enzymes to alleviate oxidative stress damage [55]. While Lactobacillus can maintain microecological balance, inhibit the growth of conditioned bacteria in the intestinal tract, and improve body immunity [56]. Tese two probiotics can be rapidly grown using fructans like INU [57].…”
Section: Regulatory Efect Of Pcps On Intestinal Microbiotamentioning
confidence: 99%
“…Firstly, probiotics can proliferate other symbiotic or probiotic strains colonized in the gut. For example, Yasushi et al () found that oral administration of Lactobacillus plantarum AN1 induced the proliferation of L. reuteri in normal mice (Yasushi et al, ). In addition to forming this “cross‐feeding” relationship with intestinal symbiotics, probiotics also can inhibit the growth of some opportunistic pathogens.…”
Section: Introductionmentioning
confidence: 99%